Neurological Sequelae due to Inborn Metabolic Diseases in Pediatric Refugees: Challenges in Treating the Untreated - Schiergens, Katharina A.; Staudigl, Michael; Borggraefe, Ingo; Maier, Esther M. (Neuropediatrics, 2018)
In the 2015 mass migration from Syria and neighboring countries, Germany received an unprecedented number of 4,76,649 asylum applications. As many of the refugees arrived in Southern Germany via the Austrian border, the city of Munich was faced with the majority of Germany's inflow of war refugees and their complex health issues. Among the refugees were a high number of children. Their main health issues were infectious diseases and surgical procedures due to trauma, but we also encountered complex chronic diseases. This report describes clinical history, signs and symptoms, diagnostics, and treatment of six pediatric patients with untreated inborn errors of metabolism (IEM): phenylketonuria, biotinidase deficiency, HMG-CoA lyase deficiency, mucopolysaccharidosis type II, and mucopolysaccharidosis type VI. Since early diagnosis and treatment is essential in IEM, both delayed diagnosis and inadequate therapy in refugee children may lead to significant brain injury, organ damage, and even death. Severe neurological sequelae in both phenylketonuria and HMG-CoA lyase deficiency could have been prevented by newborn screening. Screening programs are necessary to improve the prognoses for refugee children. European Union governments and involved health care systems should pursue early diagnosis and treatment in pediatric refugees regarding IEM to prevent neurological long-term sequelae.
Keywords: inborn errors of metabolism; neurological sequelae; refugee medicine; newborn screening; phenylketonuria; biotinidase deficiency